2016
DOI: 10.1186/s12967-016-0821-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fibroblast growth factor 15/19 and 21 on metabolism: in the fed or fasted state

Abstract: Fibroblast growth factor (FGF) 15/19 and FGF21 are two atypical members of FGF19 subfamily that function as hormones. Exogenous FGF15/19 and FGF21 have pharmacological effects, and endogenous FGF15/19 and FGF21 play vital roles in the maintenance of energy homeostasis. Recent reports have expanded the effects of FGF15/19 and FGF21 on carbohydrate and lipid metabolism. However, the regulations of FGF15/19 and FGF21 on metabolism are different. FGF15/19 is mainly secreted from the small intestine in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…FGF receptors consist of three extracellular immunoglobulin (Ig)-like domains and single transmembrane domain. Four FGF receptors, that is, FGFR-1 through FGFR-4, have been identified [2][3][4]. In order for the FGF to bind with its receptor, proteoglycans, such as heparin or heparin sulfate, are required to protect FGF from degradation and create a local reservoir of FGF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF receptors consist of three extracellular immunoglobulin (Ig)-like domains and single transmembrane domain. Four FGF receptors, that is, FGFR-1 through FGFR-4, have been identified [2][3][4]. In order for the FGF to bind with its receptor, proteoglycans, such as heparin or heparin sulfate, are required to protect FGF from degradation and create a local reservoir of FGF.…”
Section: Introductionmentioning
confidence: 99%
“…FGF15/19 and FGF21 are key members of the FGF19 subfamily. Due to the absence of a heparin binding domain, both FGF19 and FGF21 are secreted into the bloodstream and function as an endocrine factor that regulate glucose/lipid metabolism and energy homeostasis in multiple target organs, including the liver, heart, skeletal muscle, testis, kidney, blood vessel, and pancreas [4][5][6]. FGF19 and FGF21 require specific membrane-bound cofactors, α-Klotho and β-Klotho, for FGFR binding and activation.…”
Section: Introductionmentioning
confidence: 99%
“…*P < 0.05, **P < 0.01 and ***P < 0.001 by one-way ANOVA with unpaired two-tailed Student's t test fasting increased Fgf21 mRNA expression level in female soleus muscle and increased FGF21 level in plasma in both female and male mice. Emerging evidence has shown that fasting increases hepatic Fgf21 mRNA expression and plasma FGF21 level in mice [47]. FGF21 plays a role in fasting-induced muscle atrophy and weakness.…”
Section: Discussionmentioning
confidence: 97%
“…FGF15/19 induced skeletal muscle hypertrophy and blocked muscle atrophy [20]. FGF15/19 is mainly secreted from the small intestine in response to feed [47]. FGF21 has been reported negatively to regulate muscle mass and contribute towards skeletal muscle atrophy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most other members of the family, FGF19 lacks conventional heparin‐binding domain, which allows it to diffuse beyond its site of origin and thus act as endocrine hormones. In addition to promoting GB refilling, FGF19 is thought to favourably regulate lipid metabolism, glucose homeostasis, and energy expenditure via complex pathways, whose details are beyond the scope of the present review . Interestingly, the serum level of FGF19 also fluctuates daily with obvious peaks occurring 90 to 120 minutes following the postprandial rise in serum BA .…”
Section: Gb In Systemic Metabolic Regulationmentioning
confidence: 95%